Distribusi Logam Berharga Pada Mineral Pembawa Ni-Cr Pada Batuan Lateritik Metal Distribution of Ni-Cr Bearing Mineral In Lateritic Rock - Verdiansyah, Okki (Retii, 2023)
The development of the mining industry in Indonesia has increased in terms of the number and characteristics of commodities. South Konawe is on an ultramafic belt that produces laterite nickel deposits. The presence of nickel-bearing rocks in the Sulawesi area is generally in the form of laterite with horizontal enrichment in the saprolite zone. This research aims to determine the distribution patterns of nickel, iron, and chrome using laboratory analysis in the form of rock chemistry with XRF-fusion and Elemental Mapping Micro XRF Analysis (EMMA). The rock units found are ultramafic units and sandstone-siltstone units. Laterite that develops at the research location is associated with peridotite-serpentinite. The results of the analysis of bulk rock powder with XRF (fusion) are 2.5% Ni; and 11.73 % Fe. Micro-XRF analysis shows that the distribution of Fe is dominant in the matrix, Ni - Si is visible in the fragments, and Cr in the grains around the matrix forms three groups of minerals, namely Ni-limonite, Ni-serpentine, and chromite. Nickel mineralization shows the position of nickel in serpentinite and limonite, in the saprolite or saprolitic bedrock zone with the possible presence of garnierite. The highest nickel carrier is in the serpentine-smectite group associated with silica, with the highest local value interpreted as FeNi mineral or Kamasite which carries nickel reaching 46.14% Ni. In limonite, goethite-hematite is dominantly formed, which contains up to 7.3% nickel. Chromium ore or chromite minerals are also interpreted to contain up to 3.07% nickel. The presence of Ni-Fe-Cr in this rock indicates the intensive distribution of nickel during the lateritization process and is also influenced by the overburden process which causes reorientation and enrichment of elements of the same type as Ni-Fe at certain points. The results of this research can be used as a reference for the exploration and extraction of nickel or other valuable metals.